Baleiros e baleiras no velho casarão : co-educação ou escola mista no colégio militar de Porto Alegre? (RS - 1989 a 2013) - Carra, Patrícia Rodrigues Augusto (2014)
This research has been focused on the Military School in Porto Alegre (CMPA), an educational institution created for males, belonging to the military schools that are maintained by the Brazilian Army, which worked as a mono-educational school until 1989, though, since then, it began accepting girls in its student group; this research ranges from 1989 to 2013. Furthermore, the investigation has analyzed the process of accepting women as students, coming from the understanding of co-education, while praxis and educational policy, which has been committed to overcoming sexism, and aiming equal relations of gender. In addition, this study has sought for inferring whether the referred educational institution has been directed towards these ideals, seeking to implement its school mixed status to a coeducational school. Therefore, it has approached some aspects of the school culture, searching for inferring an idealized male and female, considering the existence of different masculinities and femininities, surrounding the school environment. Moreover, it has approached the perceptions of students and prior students of both sexes, about the presence of inequalities and prejudices, and, as students, men and women in construction perceiving and re-signifying gender relations in the CMPA. Mostly, the staff at CMPA has been consisted of military men, and, despite of a growing female presence in the staff, the school has maintained its male ethos. Thus, this study has concluded that, as in most of Brazilian schools, CMPA cannot be characterized as a co-educational school